1999
DOI: 10.1038/sj.bjp.0702773
|View full text |Cite
|
Sign up to set email alerts
|

Contractile 5‐HT1B receptors in human cerebral arteries: pharmacological characterization and localization with immunocytochemistry

Abstract: 1 The cerebrovascular receptor(s) that mediates 5-hydroxytryptamine (5-HT)-induced vasoconstriction in human cerebral arteries (HCA)has proven di cult to characterize, yet these are essential in migraine. We have examined 5-HT receptor subtype distribution in cerebral blood vessels by immunocytochemistry with antibodies selective for human 5-HT 1B and human 5-HT 1D receptors and also studied the contractile e ects of a range of 5-HT receptor agonists and antagonists in HCA. 2 Immunocytochemistry of cerebral ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
98
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 35 publications
7
98
0
1
Order By: Relevance
“…To address the first part of this question, small samples of cortex arterioles were obtained in conjunction with neurosurgical tumor resections or operations to remove epileptic seizure areas. These vessels indeed express ET A and ET B receptors (Nilsson et al, 1997), AT 1 (Ahnstedt et al, 2011; Ansar et al, 2009), 5-HT 1B (Nilsson et al, 1999), and thromboxane A2 (Uski et al, 1983) receptors. Moreover, freshly obtained human cerebral arteries exhibit ET-1-induced responses that were found to be similar to the responses observed in fresh rat cerebral arteries; ET-1 elicited an ET A receptor-mediated contraction with E max 112% and pEC 50 9.2, whereas S6c elicited an ET B receptor-mediated dilatation on precontraction (Nilsson et al, 1997).…”
Section: Cerebrovascular Receptor Changes In Human Arteriesmentioning
confidence: 99%
“…To address the first part of this question, small samples of cortex arterioles were obtained in conjunction with neurosurgical tumor resections or operations to remove epileptic seizure areas. These vessels indeed express ET A and ET B receptors (Nilsson et al, 1997), AT 1 (Ahnstedt et al, 2011; Ansar et al, 2009), 5-HT 1B (Nilsson et al, 1999), and thromboxane A2 (Uski et al, 1983) receptors. Moreover, freshly obtained human cerebral arteries exhibit ET-1-induced responses that were found to be similar to the responses observed in fresh rat cerebral arteries; ET-1 elicited an ET A receptor-mediated contraction with E max 112% and pEC 50 9.2, whereas S6c elicited an ET B receptor-mediated dilatation on precontraction (Nilsson et al, 1997).…”
Section: Cerebrovascular Receptor Changes In Human Arteriesmentioning
confidence: 99%
“…These drugs also inhibit dural plasma protein extravasation and action potentials in trigeminal nucleus caudalis following stimulation of the trigeminal ganglion and superior sagittal sinus, respectively (Moskowitz, 1992;Edvinsson & Goadsby, 1998;Saxena & Tfelt-Hansen, 2000). Molecular and pharmacological studies have convincingly shown that the vasoconstrictor e ect of triptans is mediated via 5-HT 1B , but not 5-HT 1D or 5-ht 1F receptors (Bouchelet et al, 1996;De Vries et al, 1998;1999b;Verheggen et al, 1998;Cohen & Schenck, 1999;Nilsson et al, 1999). On the other hand, the trigeminal neural e ects of triptans seem to involve primarily the 5-HT 1D receptor, although 5-HT 1B and 5-ht 1F receptors have also been implicated Longmore et al, 1997;McCall, 1997;Wainscott et al, 1998;De Vries et al, 1999a;Hargreaves & Shepheard, 1999;Mitsikostas et al, 1999).…”
mentioning
confidence: 99%
“…59 5-HT 1B , 5-HT 1F , and, to a smaller extent, 5-HT 1D receptor mRNAs have been identified in human cerebral arteries. 4 The 5-HT 1B receptor mRNA has also been found in human coronary arteries 7 and in peripheral blood vessels. 60,61 The 5-HT 1F mRNA receptor could only be detected in a very low amount in human coronary arteries.…”
Section: -Ht 1f Receptor Agonists and Vascular Propertiesmentioning
confidence: 99%
“…However, 5-HT 1 receptors also participate to a smaller extent in cardiac vessel constriction, 10 mostly through activation of the 5-HT 1B receptor subtype. 7 Because the vasoconstrictive potency of the triptans is low in cardiac …”
mentioning
confidence: 99%